ความสัมพันธ์ระหว่างภาระงานต่อความเหนื่อยล้าในการทำงาน โดยมีงานที่มีความหมายเป็นตัวแปรกำกับ ในพนักงานรับฝากพัสดุ องค์การขนส่งและโลจิสติกส์แห่งหนึ่งในกรุงเทพมหานคร - พรพิเศษ ศศิวิมล (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
This research aims to study the relationship between workload and work fatigue and the moderating effect of meaningful work on the relationship between workload and work fatigue. The participants of this research were 441 parcel shop counter service officers of a postal and logistics company in Bangkok. The data were collected through questionnaires including (1) general information questions (e.g., gender, work experience), (2) Workload scale including 3 dimensions (physical, mental, emotional), (3) the Work and Meaning Inventory scale: WAMI scale, and (4) the Three-Dimensional Work Fatigue Inventory: 3D-WFI scale including 3 dimensions (physical, mental, emotional). Significantly, the result showed that meaningful work negatively moderated the relationship between mental workload and mental work fatigue (β = -.24, p < .05), and negatively moderated the relationship between mental workload and emotional work fatigue (β = -.26, p < .05) significantly. This research confirmed the main hypothesis that when the employees perceived the value and the meaning of their work, it will help to reduce mental and emotional work fatigue which caused by the stress of mental workload. Therefore, the organization should support employees awareness of the meaningful work to reduce the risk of mental work fatigue and emotional work fatigue.